Numerical Study of Photoacoustic Pressure for Cancer Therapy - Thomas Grosges; Dominique Barchiesi (Applied Sciences, 2016)
A commonly used therapy for cancer is based on the necrosis of cells induced by heating through the illumination of nanoparticles embedded in cells. Recently, the photoacoustic pressure shock induced by the illumination pulse was proved and this points to another means of cell destruction. The purpose of this study is to propose a model of the photoacoustic pressure in cells. The numerical resolution of the problem requires the accurate computation of the electromagnetism, the temperature and the pressure around the nanostructures embedded in a cell. Here, the problem of the interaction between an electromagnetic excitation and a gold nanoparticle embedded in a cell domain is solved. The variations of the thermal and photoacoustic pressures are studied in order to analyze the pressure shock wave inducing the collapse of the cell’s membrane in cancer therapy.